PENGARUH PERLAKUAN DELIGNIFIKASI TERHADAP HIDROLISIS SELULOSA DAN PRODUKSI ETANOL DARI LIMBAH BERLIGNOSELULOSA - Luciasih Agustini; Lisna Efiyanti (BRIN Publishing, 2015)
Delignification signifies as the crucial stages in converting lignocelluloses into ethanol. It affects further hydrolysis and fermentation processes. This paper looks into the effects of three different delignification processes (physical-, chemical-, and biological- treatments) of lignocellulosic biomass (i.e sawdusts of sengon and oil-palm petioles) on cellulose hydrolysis and fermentation. Physically, biomass was pressurized in an autoclave which has been set for 121°C, 1 atm for 30 minutes. Chemically, 1% H₂SO₄ was added during pressurized process. Biologically, pressurized biomass was inoculated using microorganism MD-14 FB.1 obtained from INTROF-CC collection For the control, biomass stuffs without chemical, physical, and biological treatments, sustained the hydrolysis/fermentation process as well. Delignification properties with regard to α-cellulose, lignin, hemicellulose contents in the treated as well as control biomass were examined according to the ASTM procedures. The amount of glucose exhibited from cellulose hydrolysis was determined by 3,5-dinitrosalicylic acid method, while the ethanol content was determined by potassium dichromate method. Results show that in general, chemical delignification is more effective than physical and biological treatments. It shows greater yield of lignin decomposition and sugar liberation in hydrolysis. Chemical delignification treatment produced about 0.0022 - 0.4046% ethanol from the substrate fermentation. The enzyme produced from the isolations has not significantly optimized the ethanol fermentation. Further research is needed in finding the compatibility between lignocellulose biomass and enzymes which were developed from microbe isolates.